2014
DOI: 10.1021/am503295y
|View full text |Cite
|
Sign up to set email alerts
|

Double-Layer Ionomer Membrane for Improving Fuel Cell Performance

Abstract: A double-layer ionomer membrane, thin-layer Nafion (perfluorinated sulfonic acid polymer) on a sulfonated aromatic block copolymer (SPK-bl-1), was prepared for improving fuel cell performance. Each component of the double-layer membrane showed similar phase-separated morphologies to those of the original membranes. A fuel cell with the double-layer membrane exhibited lower ohmic resistance and higher cathode performance than those with the original SPK-bl-1 membrane despite their comparable water uptake and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Various strategies and materials have been developed to mitigate this issue without causing any concomitant loss in either proton conductivity or stability. 1,4,5 In this light, using of polymers with low intrinsic crossover and introducing inorganic proton conductor materials such as heteropoly acids (HPA)s have been considered extensively. An interesting class of materials for suppressing methanol permeability is the polymers containing basic groups including amine, amide, imine, and imidazole.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various strategies and materials have been developed to mitigate this issue without causing any concomitant loss in either proton conductivity or stability. 1,4,5 In this light, using of polymers with low intrinsic crossover and introducing inorganic proton conductor materials such as heteropoly acids (HPA)s have been considered extensively. An interesting class of materials for suppressing methanol permeability is the polymers containing basic groups including amine, amide, imine, and imidazole.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, Mochizuki et al covered a thick sulfonated aromatic block copolymer membrane (SPK‐ bl ‐1) with a thin layer of NAFION, significantly lowered the ohmic resistance of the SPK‐ bl ‐1 membrane and improved the cathode catalytic performance by improving the interfacial contact between the SPK‐ bl ‐1 membrane and the cathode catalyst layer. Therefore, it was concluded that the suitable design of interfacial structures between the membrane and the catalyst layer is importance for performance improvement .…”
Section: Achievements Of the Nanophase Separation Technologiesmentioning
confidence: 99%
“…In addition, Mochizuki brane (SPK-bl-1) with a thin layer of NAFION, significantly lowered the ohmic resistance of the SPK-bl-1 membrane and improved the cathode catalytic performance by improving the interfacial contact between the SPK-bl-1 membrane and the cathode catalyst layer. Therefore, it was concluded that the suitable design of interfacial structures between the membrane and the catalyst layer is importance for performance improvement [22]. In order to employ the special characteristics of materials besides NAFION, Padmavathi et al self-assembled bilayers of aminated polysulfone (APSU) and SPSU on SPEEK substrate and significantly reduced the methanol permeability [23].…”
Section: Layer-by-layer Self-assemblymentioning
confidence: 99%
“…Serious efforts have been made to eliminate such a tradeoff relationship between the proton conductivity and methanol permeability of PEMs to render them suitable for real-world DMFC applications, namely: (1) the development of alternative polymeric PEMs whose ionic clusters possess a small percolation size for methanol permeation, such as sulfonated poly(ether ether ketone), poly(arylene ether sulfone) and their derivatives as well as blends; [7][8][9][10] (2) the design of special membrane textures, like double-layered [11][12][13] and sandwichlike [14][15][16] structures via surface treatment, mainly focusing on suppressing the methanol crossover of Naon-based PEMs; (3) modication of Naon membranes by impregnating organic/ inorganic materials into the Naon matrix; etc. Of particular research interest is the third approach because it is convenient, effective and sometimes of low-cost.…”
Section: Introductionmentioning
confidence: 99%